2016
DOI: 10.1016/j.cdtm.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between quality of life and anxiety, depression, physical activity and physical performance in maintenance hemodialysis patients

Abstract: ObjectiveMaintenance hemodialysis (MHD) patients often have impaired quality of life (QOL), anxiety, depression, and reduced daily physical activity (DPA) and physical performance. The contributions of these latter factors to reduced QOL in MHD are poorly understood. We examined the association of QOL with anxiety, depression, DPA, and physical performance.MethodsSeventy-two relatively healthy adult MHD patients, vintage ≥6 months, and 39 normals of similar age range and gender distribution were studied. QOL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 34 publications
5
64
1
2
Order By: Relevance
“…Several reports indicated that increased physical activity predicted less depression [13], [28], [29] and vice versa [30][31][32]. We found a significant positive association between activity levels and SOL for depressed people.…”
Section: Physical Activity Levelssupporting
confidence: 64%
“…Several reports indicated that increased physical activity predicted less depression [13], [28], [29] and vice versa [30][31][32]. We found a significant positive association between activity levels and SOL for depressed people.…”
Section: Physical Activity Levelssupporting
confidence: 64%
“…The physiological index and anxiety of patients receiving hemodialysis have an impact on the quality of life, complications, and mortality (Borges et al, ; Li et al, ). In this study, we found that positive change in anxiety and physiological index of patients receiving hemodialysis could occur not only in the existing medical staff‐led program but also in self‐performance management of this study.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of reviewing the previous literatures, patients receiving hemodialysis have high anxiety levels, decreased self‐care, and high risk of health problems due to physiological index (Borges et al ., ; Choi & Lee, ; Feroze et al ., ; Li et al ., ; Tsai et al ., ). The self‐performance management video program developed in this study will improve self‐care knowledge and behavior, reduce anxiety, and change physiological indicators positively (Figure ).…”
Section: Introductionmentioning
confidence: 98%
“…O paciente em hemodiálise que trabalha pode produzir a percepção de pouca produtividade que ocorre por causa da dedicação ao tratamento, as reações adversas que acontecem e, em muitos casos, problemas como ansiedade e depressão que prejudicam e impedem o trabalho e a QV dessa população (LI et al, 2016).…”
Section: Discussionunclassified